THE ADDITION INTERVENTION IN CAUDAL TRACTION, MICRO WAVE DIATHERMY, TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION AND TRANSVERSE FRICTION COULD BE MORE TO REDUCE PAIN IN TENDINITIS SUPRASPINATUS - -, LUSIANA (Majalah Ilmiah Fisioterapi Indonesia, 2013)
Objective : This research aimed to identifi addition intervention in traction caudal,micro wave diathermi, transcutaneous electrical nerve stimulation and transversefriction reduce pain tendinitis supraspinatus. Method : This research is using pretest and post test control group design. Patients were randomised into two groups :the Control Group (CG) that use MWD, TENS and transverse friction is 11 patients.The Experimental Group (EG) that MWD, TENS, transverse friction and tactioncaudal is 11 patients too. Result : The result of CG test which using compare meanswith paired sample t-test, p<0,05 (p=0,000) that mean the intervention in CG is having significant to reduce pain. In the result of EG test which using comparemeans with wicolxon-test, p<0,05 (p=0,003) that mean the intervention in EG ishaving significant to reduce pain. The result test researcher using compare meantest with Independent Man witney-test, p<0,05 (p=0,003), that means there aresignificant different between EG result and CG result. In one tail hypothesis gotresult p<0,05, so it shows that intervention in EG more effective significantly thanCG in to reduce pain tendinitis supraspinatus. Conclusion : Addition intereventionin traction caudal, micro wave diathermi, transcutaneous electrical nervestimulation and transverse friction reduce pain tendinitis supraspinatus.
Keywords: tendinitis supraspinatus, reduce pain, traction caudal